Efficient Production of Acetic Acid from Nipa (Nypa fruticans) Sap by Moorella thermoacetica (f. Clostridium thermoaceticum) - Dung Van Nguyen; Pinthep Sethapokin; Harifara Rabemanolontsoa; Eiji Minami; Haruo Kawamoto; Shiro Saka (My University, 2019)
To valorize the underutilized nipa sap composed mainly of sucrose, glucose and fructose, acetic acid fermentation by Moorella thermoacetica was explored. Given that M. thermoacetica cannot directly metabolize sucrose, we evaluated various catalysts for the hydrolysis of this material. Oxalic acid and invertase exhibited high levels of activity towards the hydrolysis of the sucrose in nipa sap to glucose and fructose. Although these two methods consumed similar levels of energy for the hydrolysis of sucrose, oxalic acid was found to be more cost-effective. Nipa saps hydrolyzed by these two catalysts were also fermented by M. thermoacetica. The results revealed that the two hydrolyzed sap mixtures gave 10.0 g/L of acetic acid from the 10.2 g/L of substrate sugars in nipa sap. Notably, the results showed that the oxalic acid catalyst was also fermented to acetic acid, which avoided the need to remove the catalyst from the product stream. Taken together, these results show that oxalic acid hydrolysis is superior to enzymatic hydrolysis for the pretreatment of nipa sap. The acetic acid yield achieved in this study corresponds to a conversion efficiency of 98%, which is about 3.6 times higher than that achieved using the traditional methods. The process developed in this study therefore has high potential as a green biorefinery process for the efficient conversion of sucrose-containing nipa sap to bio-derived acetic acid.
Keywords: Oxalic Acid; Enzyme Production and Characterization